Determination Of Frequency Dependent Global Dynamic Properties Of Engine Mount - OOI , LU EAN (2004)
The dynamic properties of engine mount influence the performance of the engine mounting system. The frequency-dependent properties represented the more accurate properties of the engine mount as opposed to the frequency-independent properties model. Impact technique in the past has been used to measure the dynamic driving point stiffness in the axial position which omitted the shear properties. In this research, the impact technique is extended to measure the global dynamic properties including the dynamic shear stiffness of the engine mount.. When the engine mount is oriented in certain angles, the combination effect of dynamic compression stiffness and dynamic shear stiffness altered the global dynamic properties of the engine mount. A transformation technique is developed to include both of the dynamic stiffnesses and used them to determine the global dynamic properties of engine mount. Three different types of engine mounts are used to validate the application of the developed technique. Finally, optimization was carried out to demonstrate the effect of the global dynamic properties based on the frequency-dependent properties of engine mount. The optimum locations and orientation angles of each individual mount are identified to minimize the mean force transmissibility of the engine mounting system. The reduction of the force transmissibility showed that optimization based on the frequency-independent properties underestimated the peak transmissibility.